EVALUASI PROGRAM GERAKAN LITERASI SEKOLAH DI KELAS V SD NEGERI BLOTONGAN 02 SALATIGA - Anita Adinda Sari; Yohana Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low reading interest among elementary school students presents a significant challenge to developing a culture of literacy, a problem also observed at SDN Blotongan 02 Salatiga. Despite the implementation of literacy programs, such as designated reading corners, many students continue to exhibit low engagement in reading activities. This study aimed to evaluate the literacy program in the fifth grade of SDN Blotongan 02 Salatiga using the CIPP (Context, Input, Process, Product) evaluation model. Employing a qualitative descriptive approach, the study involved the principal, a class teacher, and three fifth-grade students as participants. Data were collected through observation, interviews, and documentation and were analyzed using data reduction, data presentation, and conclusion drawing. The results showed that: (Context) the literacy program was well-motivated by the need to improve the school's literacy culture and was supported by a conducive environment. (Input) Facilities such as reading corners were available, and teachers served as active facilitators, although time allocation remained a limitation. (Process) Literacy activities were conducted routinely, including silent reading, storytelling, and discussions, but the evaluation of writing skills was not optimal. (Product) While there was a noticeable increase in students' reading and speaking skills, their writing skills did not develop as significantly. This evaluation provides a foundation for strengthening and improving the literacy program in the future.